(3GdYQhI GdhKbi aj GdOjfs - (3GdLfGMj, GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ, J (B1262 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj fOH GdYHGO Edi WGYJg(B...(3hHYO ajbhd GdTjN MSf(B...(3dbO SCdfj ef jQLY EdjfG aj GdJbdjO Cf CUfY QSGdI hLjRI aj HYV eG JYe Hg GdHdhi ef GdCMcGe(B...s
(3BNQgG (B:s
(3hEPG GFJe eSGaQ HMGVQ Ch HGdYcS GUWMHG aj GdChdJjf hGaJQbG aj GdCNjQJjf(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B534s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis